Non-green influencers promoting sustainable consumption: Dynamic norms enhance the credibility of authentic pro-environmental posts - Buvár, Ágnes; Zsila, Ágnes; Orosz, Gábor (Frontiers in Psychology, 2023)
Social media influencers can raise awareness for sustainability, and establish norms related to a more sustainable lifestyle. Although non-green influencers can reach a wider audience, they might face credibility issues when communicating about sustainable consumption. In the present 22 online mixed method experiment (N=386), we explored the effect of two credibility-enhancing strategies (authenticity vs. referring to experts) and the presence (vs. lack of) of dynamic norms (information about how other people’s behavior is changing over time) on the perceived credibility of the post. Results indicated that referring to expert opinion enhanced perceived post credibility. However, if an authentic message was combined with dynamic norms, it reduced the frequency of mentions of the lack of credibility. Both credibility measures were positively associated with the persuasiveness of the message. These findings can contribute to the growing literature of credibility-enhancing strategies and dynamic norms. The study also provides practical suggestions for non-green influencers on effective communication of sustainable consumption.